Development of the NEST program: Nature Education for Sustainable Teaching: a training course to foster knowledge, self-efficacy, and willingness to teach outdoors - Paoletti, Daniela; Ragni, Benedetta; Rosati, Nicoletta; Cinque, Maria; Casertano, Danilo; Berenguer, Carmen; De Stasio, Simona (Frontiers in Education, 2025)
Outdoor education (OE) is increasingly recognized as a key pedagogical approach to foster holistic child development, wellbeing, and sustainable attitudes. While well established in Northern European educational systems, its adoption in Southern Europe remains limited, often due to cultural and institutional barriers and insufficient teacher preparation. This study presents the design and development of the NEST program (Nature Education for Sustainable Teaching), a structured training course aimed at enhancing student teachers’ and educators’ knowledge, self-efficacy, and willingness to teach outdoors in early childhood education. The program was developed through a participatory co-creation process that actively involved national and international experts in pedagogy and OE, from both academic and professional practice contexts. Through this collaborative process, the experts contributed to identifying priority themes and shaping the overall structure of the curriculum. The outcome is a four-module program that combines theoretical input, experiential activities, and reflective practices, and is grounded in experiential, transformative, and sociocultural learning theories. The NEST program represents an innovative and evidence-based framework for integrating OE into teacher education. By overcoming the methodological gaps of earlier initiatives, it lays the groundwork for targeted training pathways that advance a pedagogical culture more responsive to the interconnections between education and the natural environment.